2022
DOI: 10.3389/fmicb.2022.952081
|View full text |Cite
|
Sign up to set email alerts
|

Intra-species diversity of Clostridium perfringens: A diverse genetic repertoire reveals its pathogenic potential

Abstract: Clostridium perfringens is the causative agent of many enterotoxic diseases in humans and animals, and it is present in diverse environments (soil, food, sewage, and water). Multilocus Sequence Typing (MLST) and Whole Genome Sequencing (WGS) have provided a general approach about genetic diversity of C. perfringens; however, those studies are limited to specific locations and often include a reduced number of genomes. In this study, 372 C. perfringens genomes from multiple locations and sources were used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 105 publications
2
7
0
Order By: Relevance
“…Virulence factors were predicted using ABRicate (139,140) v1.0.1 (https://github.com/tseemann/ABRicate). The default virulence factor database included in ABRicate was replaced with DNA sequences from the full dataset to include all genes related to known and predicted virulence factors (141), (http://www.mgc.ac.cn/VFs/download.html).…”
Section: Methodsmentioning
confidence: 99%
“…Virulence factors were predicted using ABRicate (139,140) v1.0.1 (https://github.com/tseemann/ABRicate). The default virulence factor database included in ABRicate was replaced with DNA sequences from the full dataset to include all genes related to known and predicted virulence factors (141), (http://www.mgc.ac.cn/VFs/download.html).…”
Section: Methodsmentioning
confidence: 99%
“…Additional strain phenotypic data, including antibiograms, biochemical, or serologic strain typing also enhances available datasets to provide functional assessments of antibiotic resistance and known antigenic or biochemical properties 23,47,51 . The phenotypic analyses, particularly when conducted under a recognized international standards such as CLIA (Clinical Laboratory Improvement Amendments) 52 or ISO 15189 53 , offer means to correlate phenotypic findings from strains collected across geographic locations with genomic findings 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Targeted genome-wide phylogenetic analysis provides the capacity to understand these host-specific disease relationships, yet existing analysis has largely focused on specific pathogenic strains from one disease host or phenotype [21][22][23][24][25] or has only just recently begun to include rarely sequenced toxinotypes, such as B, C, D and E strains [26][27][28]. Large-scale genomic studies of C. perfringens have suggested that there are either four [27] or five [26] clades, two of which are disease-specific, whilst the remaining three are independent of the host or disease caused by isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted genome-wide phylogenetic analysis provides the capacity to understand these host-specific disease relationships, yet existing analysis has largely focused on specific pathogenic strains from one disease host or phenotype [21–25] or has only just recently begun to include rarely sequenced toxinotypes, such as B, C, D and E strains [26–28]. Large-scale genomic studies of C.…”
Section: Introductionmentioning
confidence: 99%